A Ten-year Cohort Study of the Association between Cardiometabolic Risk Factor Cluster and All-cause Mortality Risk among Community-dwelling Aged 55 and Over Adults - MA Wanrui, MA Qianfeng, WU Jingjie, WANG Liqun, WANG Zhizhong (Zhongguo quanke yixue, 2023)
Background Cardiometabolic risk factor cluster (CRFC) is a common health issue among aged 55 and over adults. Available studies mainly focus on the distribution of its epidemiological characteristics, but rarely assess the association between CRFC and all-cause mortality risk. Objective To explore the association between CRFC and all-cause mortality risk among community-dwelling aged 55 and over adults, to provide evidence for developing healthcare interventional programs for this group. Methods By use of typical sampling, this study selected 1 046 community-dwelling aged 55 and over adults from five urban communities in Wuzhong and Yinchuan cities of Ningxia Hui Autonomous Region during September to November 2011. And sociodemographic questionnaire survey, health check-up, ultrasonic examination, laboratory test and CRFC assessment 〔nine cardiometabolic risk factors, including central obesity, hypercholesterolemia, hypertriglyceridemia, elevated LDL-cholesterol, decreased HDL-cholesterol, hypertension, diabetes, hyperuricemia, and nonalcoholic fatty liver disease (NAFLD) 〕, were included in the multivariate Cox regression model to calculate the regression coefficient β of them after adjusting for confounders, then the coefficient of each factor was used as the weight to calculate the total risk score by adding them together were finished at baseline. The participants were followed up in 2017, 2019, and 2021 by face-to-face interview coupled with searching the national death surveillance system. Log-rank test was used to compare the survival curves for all-cause mortality plotted using the Kaplan-Meier method for tertile groups of the total cardiometabolic risk score (<P50, P50-P75, and >P75) . The Cox regression model was employed to assess the association of all-cause mortality risk with sociodemographics, cardiometabolic risk factors, the total cardiometabolic risk score, the level of the total cardiometabolic risk score, and age. Results The participants had an average age of (66.4±6.6) years (range: 55-88) at baseline. One hundred and six death cases were identified with a ten-year accumulated mortality rate of 10.13%. The individuals in >P75 group had much lower accumulated mortality rate than the other two groups, indicating that the median survival time decreased with the increase in the total cardiometabolic risk score. Multivariate Cox regression analysis showed that age, sex, living alone and education level may be associated with all-cause mortality risk (P<0.05) . After adjusting for sociodemographic variables, the multivariate Cox regression model revealed that the cardiometabolic risk factor cluster was associated with increased risk of all-cause mortality〔HR=3.04, 95%CI (1.55, 5.97) , P=0.001〕, and a dose-response effect was found that higher score was associated with an increased risk of death〔HR=2.02, 95%CI (1.16, 3.50) , P=0.013〕for > P75 when compared with risk score lower than P50) . When stratified by age group, the association only persisted among those aged 65 and over〔HR=2.79, 95%CI (1.36, 5.74) , P=0.005〕; >P75 group had higher risk of death than P50 group〔HR=1.83, 95%CI (1.02, 3.28) , P=0.042〕. Conclusion The CRFC was positively associated with all-cause mortality risk among community-dwelling aged 55 and over adults, and higher level of clustering was associated with higher all-cause mortality risk. The findings indicate that early assessment and intervention of CRFC may play a role in improving the healthcare and reducing the risk of death in this population .